2014
DOI: 10.1165/rcmb.2013-0163oc
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Ventilator-Induced Lung Edema by Inhalation of Nanoparticles Releasing Ruthenium Red

Abstract: The acute respiratory distress syndrome (ARDS), a devastating lung disease that has no cure, is exacerbated by life-supportive mechanical ventilation that worsens lung edema and inflammation through the syndrome of ventilator-induced lung injury. Recently, the membrane ion channel transient receptor potential vanilloid 4 (TRPV4) on alveolar macrophages was shown to mediate murine lung vascular permeability induced by high-pressure mechanical ventilation. The objective of this study was to determine whether inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…This would suggest that administration a second dose of RR around the 8-12 hr time point.. This agrees with what was reported when inhaled RR was used to prevent ventilator-induced lung edema, where the protection provided by RR alone was efficient for less than two hours unless the RR therapy was administered in a sustained released delivery system using inhaled poly-lactic-co-glycolic acid (PLGA) nanoparticles (Jurek, Hirano-Kobayashi et al 2014). …”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…This would suggest that administration a second dose of RR around the 8-12 hr time point.. This agrees with what was reported when inhaled RR was used to prevent ventilator-induced lung edema, where the protection provided by RR alone was efficient for less than two hours unless the RR therapy was administered in a sustained released delivery system using inhaled poly-lactic-co-glycolic acid (PLGA) nanoparticles (Jurek, Hirano-Kobayashi et al 2014). …”
Section: Resultssupporting
confidence: 83%
“…TRP channels are involved in signal transduction of various pathways following activation and involve cells that are not directly exposed to air, e.g. macrophages, endothelial cells, vascular endothelial cells (Freichel, Suh et al 2001, Alvarez, King et al 2006, Willette, Bao et al 2008, Grace, Baxter et al 2014, Jurek, Hirano-Kobayashi et al 2014). CG is hydrophobic in nature and, therefore, it passes through the upper respiratory tract with less absorption and concentrates mostly in the deep lung to cause toxicity in the alveoli and microvascular system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these data, one recent study showed that the inhalation of nanoparticles (NPs) containing the TRPV4 inhibitor ruthenium red prevented VILI in mice, emphasizing the importance of macrophage function and highlighting nanoparticles as potential vehicle-delivering agents 38 .…”
Section: Endothelial Cellsmentioning
confidence: 76%
“…In CF, TRPV4 appears to play paradoxical roles in CBF/mucociliary clearance and epithelial cell pro-inflammatory chemokine (IL-8/KC) secretion ( 317 , 318 ). Depending on the underlying etiology, TRPV4 may play different roles in ARDS ( 307 , 310 , 314 , 319 ). Also, in pulmonary fibrosis, TRPV4 has been shown to mediate the mechano-sensing that drives myofibroblast differentiation and experimental lung fibrosis in mice ( 308 ).…”
Section: Regulation Of Afcmentioning
confidence: 99%